Are practitioners underprepared?. (2nd May 2022) - Mason, Gill; Fawkes, Lauren; Knight, Louise
Abstract : Practitioners are often required to support children to deepen their knowledge and understanding of challenging and complex topics. The war in Ukraine is no different. Below, Kids Planet reflect on whether they think practitioners are appropriately prepared to navigate such sensitive conversations with children.